The imperatives of the digital economy in the development of the enterprise management methodology - Tkachenko, V.; Klymchuk, M. (Ways to Improve Construction Efficiency, 2019)
Digital transformations of economic systems at the levels of the world economy, economies of individual countries, industries, enterprises are realities of our time, which cause the need to adapt enterprises to new conditions of functioning. The purpose of the article is to investigate the impact of digital economy basic principles on the formation of enterprise management methodology, identify imperatives of digitization of construction enterprises through the prism of vectors and forms of realization of investment and innovation activity, because in the current economic conditions one of the important factors of effective functioning of the production and economic system in the long-term digital transformation and an effective mechanism for attracting investment to realize it. Research methods are comparative analysis, analogy method, and content analysis based on the cognitive economy research apparatus. The article, based on the results of content analysis of digital transformations, highlights the general and distinctive features of the implementation of strategic documents that ensure the formation of the digital economy in different countries of the world. The identified patterns have made it possible to argue that the overall digital economy development strategy in Ukraine is in line with global trends. The imperatives of digitization of construction enterprises through the prism of vectors and forms of realization of investment-innovative activity are offered, because in the current economic conditions one of the important factors of effective functioning of the production and economic system in the long term is digital transformation and effective mechanism of attracting investments for its realization. According to the results of the research, the following imperatives for the development of digitalization of construction enterprises are proposed and considered in detail: investment-innovative, economic, social, managerial, environmental. The identified patterns have made it possible to argue that the overall digital economy development strategy in Ukraine is in line with global trends. The need for intensification of innovation and investment activity in the field of digital technology implementation has been identified.